2010
DOI: 10.1139/e10-026
|View full text |Cite
|
Sign up to set email alerts
|

Application of modern 2-D and 3-D seismic-reflection techniques for uranium exploration in the Athabasca BasinThis article is one of a series of papers published in this Special Issue on the themeLithoprobe — parameters, processes, and the evolution of a continent.

Abstract: Seismic-reflection techniques have been applied in several studies over the last 20 years as a uranium-exploration tool within the Athabasca Basin and have been utilized to provide the larger structural context for known uranium deposits within the basin. At the crustal scale, deposits within the eastern Athabasca Basin are shown to be associated with deep-seated shear zones that originated during Trans-Hudson orogeny and have subsequently been reactivated during and subsequent to deposition of the basin-fill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Annesley and Madore (1994) observed that the Wollaston-Mudjatik boundary, in the Wollaston Lake area, marks an abrupt change of lithology and structural style. However, to the southwest, Annesley et al (2005, and references therein), Gyorfi et al (2007), Hajnal et al (2010), among others, showed that this domain boundary is a highly heterogeneous transition zone both across and along strike.…”
Section: Significance Of the Wollaston-mudjatik Transition Zonementioning
confidence: 94%
See 1 more Smart Citation
“…Annesley and Madore (1994) observed that the Wollaston-Mudjatik boundary, in the Wollaston Lake area, marks an abrupt change of lithology and structural style. However, to the southwest, Annesley et al (2005, and references therein), Gyorfi et al (2007), Hajnal et al (2010), among others, showed that this domain boundary is a highly heterogeneous transition zone both across and along strike.…”
Section: Significance Of the Wollaston-mudjatik Transition Zonementioning
confidence: 94%
“…1), during the EX-TECH IV project (Hajnal et al 2010). This reflector below the Athabasca unconformity is referred to as the "Dipping Reflector" (DR) in Hajnal et al (2007).…”
Section: M1-d1 Event: Peak Metamorphic Conditions Of Burial and Signimentioning
confidence: 99%
“…Seismic methods are well-suited to exploration in this setting as the uranium deposits typically occur near the unconformity that separates an undeformed clastic sequence from underlying metamorphic crystalline basement rocks. As summarized by Hajnal et al (2010), the first successful demonstration of high-resolution seismic methods during the Lithoprobe project spawned several subsequent 2D exploration surveys at Shea Creek in 1997, McArthur River in 2004 (e.g., Gyorfi et al, 2007;, Russell and Moore Lake in , and Midwest Northeast and Millennium 3D surveys in 2007(e.g., Juhojuntti et al, 2012Wood et al, 2012). Hathor Resources performed the first seismic-based major uranium discovery in 2007, leading to a 2010 total resource of 12.1 million pounds of U 3 O 8 .…”
Section: Seismic Methods For Mineral Exploration Wc179mentioning
confidence: 99%
“…Sudbury impact structure, Creighton 402 Orebody; Eaton et al 2010), uranium deposits (e.g. Athabasca Basin, McArthur River Mine;Hajnal et al 2010), and diamondiferous kimberlites (e.g. Diavik, A154 pipe; Snyder and Grütter 2010).…”
Section: Possible Applications To Mineral Explorationmentioning
confidence: 99%